Clinical Manifestations, Diagnosis, Management and Prevention of Cervical Cancer - Sastraningsih Setiawati; Yunita Hapsari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The second most prevalent cancer in women and one that may be mainly prevented or treated if discovered at an early stage, cervical cancer is a serious health concern worldwide, particularly in Indonesia. This literature review aims to provide related information about clinical manifestations, diagnosis, management and prevention of cervical cancer. We searched online databases and used review articles, research, guidelines from professional organizations, such as POGI from Indonesia and FIGO from London. The disease's clinical manifestations often appear in advanced stages and can include abnormal vaginal bleeding, pelvic pain, and pain during intercourse. Diagnosis typically involves a multi-step process beginning with physical examination, Pap smear tests, HPV testing, and possibly leading to colposcopy and biopsy procedures for confirmatory analysis. Management strategies for cervical cancer range from conservative watch-and-wait approaches in early-stage disease to more aggressive interventions such as surgery, radiation, and chemotherapy in more advanced cases. Prevention strategies have centered on HPV vaccination and regular screening tests, both of which remain underutilized in regions like Indonesia. Despite the availability of effective preventative and therapeutic measures, the high incidence and mortality rates emphasize the critical need for enhanced public health efforts to increase screening and vaccination rates, improve access to treatment, and promote education on cervical cancer. Cervical cancer usually does not appear until the cancer has reached an advanced stage trough increased awareness, education, and access to screening and treatment services, the burden of cervical cancer can be reduced.